The Two-Component System RsrS-RsrR Regulates the Tetrathionate Intermediate Pathway for Thiosulfate Oxidation in Acidithiobacillus caldus - Wang, Zhao-Bao; Li, Ya-Qing; Lin, Jian-Qun; Pang, Xin; Liu, Xiang-Mei; Liu, Bing-Qiang; Wang, Rui; Zhang, Cheng-Jia; Wu, Yan; Lin, Jian-Qiang; Chen, Lin-Xu (Frontiers in Microbiology, 2016)
Acidithiobacillus caldus (A. caldus) is a common bioleaching bacterium that possesses a sophisticated and highly efficient inorganic sulfur compound metabolism network. Thiosulfate, a central intermediate in the sulfur metabolism network of A. caldus and other sulfur-oxidizing microorganisms, can be metabolized via the tetrathionate intermediate (S4I) pathway catalyzed by thiosulfate:quinol oxidoreductase (Tqo or DoxDA) and tetrathionate hydrolase (TetH). In A. caldus, there is an additional two-component system called RsrS-RsrR. Since rsrS and rsrR are arranged as an operon with doxDA and tetH in the genome, we suggest that the regulation of the S4I pathway may occur via the RsrS-RsrR system. To examine the regulatory role of the two-component system RsrS-RsrR on the S4I pathway, ΔrsrR and ΔrsrS strains were constructed in A. caldus using a newly developed markerless gene knockout method. Transcriptional analysis of the tetH cluster in the wild type and mutant strains revealed positive regulation of the S4I pathway by the RsrS-RsrR system. A 19 bp inverted repeat sequence (IRS, AACACCTGTTACACCTGTT) located upstream of the tetH promoter was identified as the binding site for RsrR by using electrophoretic mobility shift assays (EMSAs) in vitro and promoter-probe vectors in vivo. In addition, ΔrsrR, and ΔrsrS strains cultivated in K2S4O6-medium exhibited significant growth differences when compared with the wild type. Transcriptional analysis indicated that the absence of rsrS or rsrR had different effects on the expression of genes involved in sulfur metabolism and signaling systems. Finally, a model of tetrathionate sensing by RsrS, signal transduction via RsrR, and transcriptional activation of tetH-doxDA was proposed to provide insights toward the understanding of sulfur metabolism in A. caldus. This study also provided a powerful genetic tool for studies in A. caldus.